MATHEMATICS EDUCATION AND DIGITAL TECHNOLOGIES: REFLECTING ON THE POTENTIAL FOR MATHEMATICS EDUCATIONAL PROCESSES - Freitas, Danton de Oliveira; Costa, Emily Fabiane Silva (Seven Editora, 2025)
The advancement of digital technologies, in various contexts of our society, where individuals operate, influence, and modify human interactions, is directly related to the cultural, political, and economic needs of humanity. Educational spaces/processes are one of these contexts where these technologies are being introduced and expanding their reach. In this context, this paper proposes to reflect on the contributions made possible by digital technologies to mathematics education processes, considering the importance of understanding their use within school spaces as a support tool for mathematics education processes and their potential that emerges from social practices. However, we cannot consider these tools as the complete solution for all mathematics education processes because they may not be developed for educational purposes, but their use can contribute to bringing students closer to social reality from the moment that the didactic-pedagogical planning provides opportunities that stimulate reflections on themes related to society, creativity, autonomy, spatial notions, and the construction of mathematical knowledge. DOI: https://doi.org/10.56238/sevened2025.038-056